Sleep disruption and duration in late pregnancy is associated with excess gestational weight gain among overweight and obese women. Issue 2 (15th February 2017) - Gay, Caryl L.; Richoux, Sarah E.; Beebe, Kathleen R.; Lee, Kathryn A.
Abstract: Background: Poor sleep during pregnancy has been associated with poorer birth outcomes. High body mass index (BMI) is often associated with poor sleep, but little is known about the relationship between gestational weight gain and sleep in late pregnancy. The purpose of this study was to evaluate the relationships of both gestational weight gain and pre‐pregnancy BMI to objective and subjective measures of sleep during late pregnancy. Methods: Pregnant women (n=128) were recruited from prenatal clinics and childbirth classes primarily serving low‐income women. Their sleep (disruption and duration) was objectively assessed in their last month of pregnancy with 72 hours of wrist actigraphy monitoring. Their perceived sleep quality was assessed with the Pittsburgh Sleep Quality Index. Pre‐pregnancy and late pregnancy height and weight were assessed by self‐report and used to calculate BMI and gestational weight gain, which were then grouped into standardized categories. Results: Mean Pittsburgh Sleep Quality Index score was 6.8 ± 3.1 (range 2–16). Sixty percent had excess gestational weight gain and it was associated with poorer perceived sleep quality, but was unrelated to objective measures of sleep duration and disruption. Pre‐pregnancy BMI was unrelated to all sleep parameters. However, analyses of the interaction of pre‐pregnancy BMI and gestational weight gain indicated that excess weight gain was associated with shorter sleep duration and more sleep disruption, but only among women who were overweight before pregnancy. Conclusion: Pregnancy is an opportunity to promote long‐term women's health with a better understanding of the relationship between weight management and healthy sleep habits.